Severe congenital generalized exfoliative erythroderma in newborns and infants: a possible sign of Netherton syndrome - Haußer-Siller, Ingrid; Anton-Lamprecht, Ingrun (Pediatric dermatology, 1996)
Abstract: We examined skin biopsy specimens from 17 of 19 newborns or infants with generalized ichthyosiform, exfoliative, seborrheic, or psoriasiform erythroderma. The specimens showed similar characteristic but nonspecific and therefore, at first sight, uninformative histologic features. Morphologically, the skin was affected overall with a persistent outbreak of eczema-like eruptions of subacute or chronic dermatitis. Pronounced dermal inflammatory processes were obvious by their perivascular and interstitial presence as well as exocytosis of lymphocytes, macrophages, and neutrophils. Epidermal barrier function was impaired by the highly suppressed terminal differentiation, with thin or in part completely absent stratum corneum, decrease of keratin filaments, decrease or lack of kera-tohyalin granules, and of keratinosomes containing stacks of lipid membranes. As a result, the formation and discharge of epidermal barrier lipids from the keratinosomes that normally provide intercellular lamellar sheets at the granular-horny layer interface contributing to the epidermal barrier, was highly disturbed. The concomitant loss of water, electrolytes, and proteins by fluid exudation caused the patients severe metabolic problems and recurrent infections. The suspicion of Netherton syndrome was eventually confirmed in 18 patients by light microscopic demonstration of bamboo hairs (trichorrhexis invaginata), mostly from the scalp, but also in velius hairs and eyelashes. Atopy actually belongs to the symptom triad defining Netherton syndrome and is, in our opinion, primarily responsible for the pathologic events within the skin and of the keratinizing parts of the growing hair shafts. Differential expression of the atopic condition determines the appearance of the keratinization disorder of the skin, namely, severe, generalized, exfoliative erythroderma or milder forms of ichthyosis linearis circumflexa Comèl. Retinoid treatment seems to be contraindicated in these conditions since their biopharmacologic effects involve suppression of terminal differentiation, which is the proper pathognomonic event. In six patients the condition had a fatal course within months because of hypernatremia, recurrent infections, failure to thrive, and sepsis. Our aim is to call attention to and reaffirm that in congenital or early infantile cases of generalized exfoliative erythroderma, Netherton syndrome should be suspected as the underlying disease.
Gesehen am 27.09.2023